Efficacy of the Applied Natural Enemies on the Survival of Colorado Potato Beetle Adults - Půža, Vladimír; Nermuť, Jiří; Konopická, Jana; Skoková Habuštová, Oxana (Insects, 2021)
Colorado potato beetle Leptinotarsa decemlineata is among the most destructive pests of potatoes quickly developing resistance to traditional insecticides. In the present study, we tested the effect of various species and strains of entomopathogenic nematodes on CPB adults, and subsequently, the most effective nematodes were applied alone and in combination with entomopathogenic fungus B. bassiana in pots with potato plants and in the field and their effect on the number of emerging adults was evaluated. In the experimental infections, both the nematode invasion and pathogenicity were variable, and, in several strains, the mortality reached 100%. In pot experiments, soil application of nematodes S. carpocapsae 1343 and S. feltiae Jakub and fungus significantly decreased numbers of emerging CPB adults, while, after the application on leaves, only fungal treatment was effective. The field application of fungus B. bassiana significantly decreased the number of emerging CPB adults in comparison to control sites by ca. 30% while the effect of nematodes and the nematodes-fungus combination was not significant. In conclusion, we demonstrate the necessity of thorough bioassays to select the most effective nematode strains. Entomopathogenic nematodes have the potential to effectively decrease the emergence of CPB adults, but further research is needed to improve the effectiveness in the field.
Keywords: Colorado potato beetle; Steinernema; Beauveria; entomopathogenic fungi; field application; entomopathogenic nematodes